Hubungan Tipe Kepribadian Dengan Prestasi Belajar Pendidikan Agama Islam Pada Siswa Kelas V SD. Inpres Panaikang 11 Kota Makassar - Ida Asriwati; Bunyamin, Andi; Pilo, Nashiruddin (Journal of Gurutta Education, 2023)
This study aims to determine the method of identifying the student's personality type, knowing the method of assessing learning achievement, and knowing whether there is a relationship between personality type and learning achievement (PAI) in fifth grade elementary school students. Inpres Panaikang 11, Makassar City. The type of this research is qualitative research with exploratory description. The research population is all elementary school students. Inpres Panaikang 11, totaling 309 students, while the research sample was all Class V students, totaling 59 students. In the results of the study, it was found that the percentage of learning achievement (high score) for each personality type was choleric (first highest), sanguine (second), melancholic (third), and phlegmatic (lowest). The top 3 ranks with the highest scores are filled with choleric and melancholy. In the second place is choleric and melancholy, and in the third is Sanguinis. It was found that there was a pattern of relationship between personality type and PAI learning achievement. The pattern of the relationship is that there are multiple factors that cause it to go in one direction or make it stronger. It is hard to figure out how strong the relationship is